2014
DOI: 10.1080/19475411.2014.904828
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization on the thermal conductivity of graphene–polymer nanocomposites

Abstract: Exploring thermal transport in graphene-polymer nanocomposite is significant to its applications with better thermal properties. Interfacial thermal conductance between graphene and polymer matrix plays a critical role in the improvement of thermal conductivity of graphene-polymer nanocomposite. Unfortunately, it is still challenging to understand the interfacial thermal transport between graphene nanofiller and polymer matrix at small material length scale. To this end, using nonequilibrium molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…36,37 When graphene is sufficiently covered with the organic polymer, the thermal conductivity of the graphene/polymer composites is reduced to a minimum of four orders of magnitude due to the low thermal conductivity of the polymer. 38 Therefore, we expect that the ZT value of the RCG/P hybrid lm is much larger than that of the graphene lm. Bending tests of the graphene lm and RCG/P hybrid lms A bending test of the RCG/P hybrid lms was conducted to evaluate the lms' bending stability.…”
Section: -33mentioning
confidence: 99%
“…36,37 When graphene is sufficiently covered with the organic polymer, the thermal conductivity of the graphene/polymer composites is reduced to a minimum of four orders of magnitude due to the low thermal conductivity of the polymer. 38 Therefore, we expect that the ZT value of the RCG/P hybrid lm is much larger than that of the graphene lm. Bending tests of the graphene lm and RCG/P hybrid lms A bending test of the RCG/P hybrid lms was conducted to evaluate the lms' bending stability.…”
Section: -33mentioning
confidence: 99%
“…NEMD simulations of ITC across graphene-PE interfaces were conducted using LAMMPS package [23]. An ab initio force field, polymer consistent force field (PCFF) [24] was chosen to describe all the interatomic interactions of nanocomposite model [22,[25][26][27][28]. All nanocomposite models were firstly relaxed in iso-thermal-isobaric (NPT) ensemble at temperature T = 300 K and pressure P = 1 atm for 1 ns.…”
Section: Materials and Numerical Proceduresmentioning
confidence: 99%
“…25,[44][45][46][47][48][49][50][51] Results from analytical models based on an effective medium theory, 44,51 a micromechanical modeling approach 45,46 as well as atomistic simulations 25,[47][48][49][50][51] have emphasized that functionalized CNTs in a polymer matrix modify the thermal properties of the interfacial polymer phase relative to l of its bare parent system. 25,[44][45][46][47][48][49][50][51] Results from analytical models based on an effective medium theory, 44,51 a micromechanical modeling approach 45,46 as well as atomistic simulations 25,[47][48][49][50][51] have emphasized that functionalized CNTs in a polymer matrix modify the thermal properties of the interfacial polymer phase relative to l of its bare parent system.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations and an effective medium theory predicted an increase in the thermal conductivity by roughly a factor of two in a composite containing a functionalized single-walled CNT. Furthermore, for functionalized graphene-polymer composites, Wang et al 50 considered different grafting densities of linear hydrocarbon chains in their analysis of composites containing monolayer graphene. Recently -in combination with other investigators -Khare et al 48 have shown a similar behavior.…”
Section: Introductionmentioning
confidence: 99%